Root fungal endophytes: identity, phylogeny and roles in plant tolerance to metal stress. Issue 4 (April 2021) - Barberis, Louise; Michalet, Serge; Piola, Florence; Binet, Philippe
Abstract: Metal trace elements accumulate in soils mainly because of anthropic activities, leading living organisms to develop strategies to handle metal toxicity. Plants often associate with root endophytic fungi, including nonmycorrhizal fungi, and some of these organisms are associated with metal tolerance. The lack of synthetic analyses of plant-endophyte-metal tripartite systems and the scant consideration for taxonomy led to this review aiming (1) to inventory non-mycorrhizal root fungal endophytes described with respect to their taxonomic diversity and (2) to determine the mutualistic roles of these plant-fungus associations under metal stress. More than 1500 species in 100 orders (mainly Hypocreales and Pleosporales) were reported from a wide variety of environments and hosts. Most reported endophytes had a positive effect on their host under metal stress, but with various effects on metal uptake or translocation and no clear taxonomic consistency. Future research considering the functional patterns and dynamics of these associations is thus encouraged.